TENDENCES IN GERIATRIC WARD DESIGN – ELDERLY FRIENDLY COMPONENTS OF SPACE - Szewczenko, Anna Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
In the article the most significant issues in geriatric ward design are presented, those which allows to support the functional activity of elderly patients. In contemporary healthcare architecture the tendency of breaking the institutionalization of hospitals are observed, moreover, the needs of patients are the basis for design as patient-centred design. State of art related to healing environment gives the basis for increasing the role of architectural solutions, which give positive support to the patient’s psychosocial condition in treatment process.